Understanding in mathematics - Sierpinska, Anna. (London ; Washington, D.C. : Falmer, 1994)
The concept of understanding in mathematics with regard to mathematics education is considered in this volume, the main problem for mathematics teachers being how to facilitate their students' understanding of the mathematics being taught.
Book Cover; Title; Contents; List of Figures; Acknowledgments; Preface by Series Editor; Introduction; Understanding and Meaning; Meaning; Components and Conditions of an Act of Understanding; What Could Be an Act of Understanding?; Components of an Act of Understanding; Psychological Conditions of an Act of Understanding; Social Conditions of an Act of Understanding; What Understanding Is Not; Processes of Understanding; Reasonings; Explanation and Understanding; The Role of Example and the Medium in Which It Is Presented for Understanding; Figures of Speech in Understanding.
Includes bibliographical references (pages 170-182) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Mathematics -- Study and teaching -- Psychological aspects; Comprehension; Education -- Curricula; Mathematics -- Study and teaching -- Psychology; Curriculum; Mathématiques -- Étude et enseignement -- Psychologie; Compréhension.; Programmes d'études.; Mathématiques -- Étude et enseignement -- Aspect psychologique; curricula; EDUCATION -- Educational Psychology; Mathematics -- Study and teaching -- Psychology; Education -- Curricula; Comprehension; Mathematics -- Study and teaching -- Psychological aspects; Schools -- Curriculum -- Mathematics